A feasibility study to measure magnetocardiography (MCG) in unshielded environment using first order gradiometer. (January 2020) - Swain, Pragyna parimita; Sengottuvel, S.; Patel, Rajesh; Mani, Awadhesh; Gireesan, K.
Highlights: Measurement of MCG with First order gradiometer in unshielded environment. Noise cancellation capability of gradiometer augmented by EEMD technique. Detailed comparison of MCG measured in shielded and unshielded sites. Method used is suitable for unshielded MCG for deeper cardiac source estimations. Abstract: Measurement of weak magnetic fields generated by the electrical activity of the heart is known as magnetocardiogram (MCG). MCG is usually measured using highly sensitive Superconducting Quantum Interference Devices (SQUIDs) inside a Magnetically Shielded Room (MSR). Since MCG signals have a relatively higher amplitude, researchers have attempted to measure MCG in poorly shielded or even in unshielded environments using higher order gradiometers to cancel excess noise. However, they also attenuate signals of interest, especially, those originating from deeper sources. Here, we report a feasibility study to examine the suitability of use of First Order Gradiometers (FOG) to measure MCG in a totally unshielded environment. Usually, conventional noise reduction methods involve averaging of a large number of cardiac cycles aligned by R-peak time instants derived from a simultaneously recorded electrocardiogram (ECG). In addition to this, here we employ a novel noise reduction approach based on Ensemble Empirical Mode Decomposition (EEMD) technique to manage the fall in Signal to Noise Ratio (SNR) in unshielded environment. The study demonstrated an improvement in SNR of about 18 dB in unshielded setup measured using a four channel low TC -DC SQUID system when tested on eight healthy subjects and one subject with a known cardiac dysfunction. MCG traces were measured across different locations on the thorax and the spatial distribution of cardiac magnetic field is visualized using magnetic field maps. The resulting data have been critically evaluated and compared with those derived from MCG measurements made inside the MSR and encourages its clinical utility.